Desain Eksperimen TUF Dalam Peningkatan Kualitas Garam Olahan Limbah Produksi Es dengan Metode Taguchi di PT. Putra Maesa Persada - Susanti Dhini Anggraini; Abdul Wahid Nuruddin; Krishna Tri Sanjaya; Anggia Kalista; Moh Muhyidin Agus Wibowo; Dani Hardian Kusuma (JATI UNIK : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
Indonesia has salt resources in seawater along the Java Sea coast. However, the high salt content in seawater causes difficulties for various industries that use seawater as their raw material. A Taguchi experimental design using TUF filters was carried out to determine the best TUF filter composition in producing high-quality salt. The factors considered were the compositions of three materials, namely crushed coral, charcoal, and palm fibers. The results obtained for the sample filters were analyzed using one-way ANOVA, Minitab, and the Signal-to-Noise Ratio (SNR) method. The optimal TUF filter composition was found to be 450g finely crushed coral, 350g finely crushed charcoal, and 30g palm fibers. The study results revealed that the best factor for improving salt quality was crushed coral, with a contribution of 65.63842% and an F-value of 109.3333. Charcoal also provided a significant contribution of 24.40453% with an F-value of 40.65041. However, palm fibers did not contribute significantly to improving salt quality. The optimal TUF filter composition can help improve salt quality and increase productivity while reducing costs for various industries such as food production and preservation. The optimal composition of 450g of crushed coral, 350g of charcoal, and 30g of palm fibers can significantly improve the quality of salt production. In conclusion, the use of TUF filters with the optimal composition of 450g crushed coral, 350g charcoal, and 30g palm fibers can significantly improve salt quality. This study provides insight into the potential applications of TUF filters and should encourage further exploration of the technology's potential in various industries.